2021
DOI: 10.3390/jpm11090884
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noninvasive Respiratory Management in Patients with Severe COVID-19 Pneumonia

Abstract: Acute hypoxemic respiratory failure is the principal cause of hospitalization, invasive mechanical ventilation and death in severe COVID-19 infection. Nearly half of intubated patients with COVID-19 eventually die. High-Flow Nasal Oxygen (HFNO) and Noninvasive Ventilation (NIV) constitute valuable tools to avert endotracheal intubation in patients with severe COVID-19 pneumonia who do not respond to conventional oxygen treatment. Sparing Intensive Care Unit beds and reducing intubation-related complications ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 140 publications
0
16
0
Order By: Relevance
“…In COVID-19 patients, NIRS has been proposed to avoid intubation and provide early post-extubation respiratory support [ 6 , 7 , 18 ]. However, the potential risk of P-SILI may outweigh the benefits of NIRS (e.g., reduced risk of ventilator-associated pneumonia, sedation-related adverse effects) [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 patients, NIRS has been proposed to avoid intubation and provide early post-extubation respiratory support [ 6 , 7 , 18 ]. However, the potential risk of P-SILI may outweigh the benefits of NIRS (e.g., reduced risk of ventilator-associated pneumonia, sedation-related adverse effects) [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 pneumonia causes significant deterioration in patients’ respiratory conditions, the percentage of patients who required escalation of oxygen therapy to the active therapy was higher than prior to COVID-19. In the era of COVID-19, the reports claim that HFNO has been used in 23–64% of patients with severe COVID-19 pneumonia [ 23 ]. Data on HFNO in COVID-19 indicate that its use has reduced the necessity of endotracheal intubation by between 44% and as much as 64% but has had no clear effect on mortality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the era of COVID-19, the reports claim that HFNO has been used in 23–64% of patients with severe COVID-19 pneumonia [ 23 ]. Data on HFNO in COVID-19 indicate that its use has reduced the necessity of endotracheal intubation by between 44% and as much as 64% but has had no clear effect on mortality [ 23 ]. The subanalysis of the HOPE COVID-19 registry indicated that more than half of the patients who received NIV due to COVID-19 pneumonia survived without intubation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the HFNC group obtained a significantly better successful outcome and greater patient satisfaction compared with the NRM group. Although the effectiveness of HFNC in COVID-19 is supported by prior research from across the world, [10 12] this is one of the first RCTs comparing NRM and HFNC. Nevertheless, comparing HFNC with NIV such as continuous positive airway pressure would have been more appropriate in this study.…”
Section: Editorialmentioning
confidence: 90%
“… [14] Having a unit mplementation plan and algorithm for the use of HFNC can offer clear guidelines for less experienced staff on the ground. [12] In the SA setting, HFNC played a significant role in the pandemic response, as it was provided at field hospitals and secondary level hospitals, which relieved significant burden on tertiary-level ICU facilities. [15 , 16] The main limiting factor is that of reliable oxygen supply and its associated costs.…”
Section: Editorialmentioning
confidence: 99%